The gravitational force acts as the centripetal force for circular motion:
\[
F_{\text{gravity}} = F_{\text{centripetal}}.
\]
The gravitational force between two particles is expressed as:
\[
F = \frac{G M_1 M_2}{d^2},
\]
where:
- \( G \) is the gravitational constant,
- \( M_1 = M_2 = m \),
- \( d = 2a \), the distance between the two particles.
Substitute \( M_1 = M_2 = m \) and \( d = 2a \):
\[
F = \frac{G m^2}{(2a)^2} = \frac{G m^2}{4a^2}.
\]
For circular motion:
\[
F = m \omega^2 r,
\]
where \( r = a \). Equating \( F \):
\[
\frac{G m^2}{4a^2} = m \omega^2 a.
\]
Simplify the equation:
\[
\omega^2 = \frac{G m}{4a^3}.
\]
Take the square root to find \( \omega \):
\[
\omega = \sqrt{\frac{G m}{4a^3}}.
\]
Final Answer:
\[
\boxed{\sqrt{\frac{G m}{4a^3}}}
\]